(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article analyzes the influence of privatization, which is the main tool for the formation of market relations in the energy sector. The authors found that as a result of the privatization of energy assets in Ukraine, it was not possible to maintain a balance of interests of the state, business and society. The state monopoly was replaced by oligopoly, consumer sovereignty was not secured, and responsibility for energy security is distributed unevenly between business and government. Because of the lack of coordination of policy objectives, privatization did not use the investment resource for energy development, mechanisms for the return of invested funds, which were tested by world experience, were not involved. Completion of privatization should take place after the adoption of a number of decisions related to the institutional framework for the development of electricity market, the development of privatization conditions and contracts with potential investors, measures to ensure the energy security of the state. Reliability of energy supply in the context of further development of private property in the energy sector will be determined by the effectiveness of state regulation in this area, the ability to prevent uncompetitive behavior of market participants. The delay in moving to the European energy model encourages business entities (including sectored monopolists) to lobby their own projects in the government bodies that contradict the established principles of market functioning. The risk of transforming the transitional measures into permanent ones is no less a threat. At the same time, the incompleteness of the transition from the administrative to the market model of regulation not only hampers the development of the world’s best business practices by business entities, but also undermines the credibility of government actions. To remedy the situation, it is necessary to accelerate the formation of the institutional and institutional base that ensures the functioning of the energy market in accordance with its new model; to stop administrative interference of the state in the activity of subjects of energy markets, regardless of forms of ownership; to complete privatization of energy assets; to refuse cross- subsidization; to complete the process of monetization of subsidies. Civil society institutions should become a lever to control management decisions and not to distort the norms of the Law of Ukraine "On the Electricity Market" at the stage of its implementation.